The correct answer is B
Statements: J < K, J < L, L > M
Conclusions: I. J < M II. L = J
...Statements: Q ≥ R > U; R ≤ S; U ≥ B
Conclusions: I. U < Q II. S > B
...Statement: M > N < P = Q ≥ R; Q ≥ T
Conclusion:
1. R≥T
2. N < T
...Statements: I ≥ E = S > J < N > V > Q ≤ O
Conclusion
I: I > S
II: Q < N
Given statement shows the relation between different elements followed by two conclusions.Â
Statement: B2 = T4 < E3 ≤ G5 > F6 = H7 > Q8Â
...Statements: H ≤ I ≥ K> L; M > J ≥ N ≥ I
Conclusions:
I. J ≥ K
II. M > L
Statements:Â R @ C % L #Â X & P $ AÂ # W; Q $ L @ X
Conclusions:
I. W @ L
II. A # Q
III. R @ X
...Statements: R © K, K * N, N $ J, J % H
Conclusions: Â Â Â Â I.R $ NÂ Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â II.J @ KÂ Â Â Â Â Â Â Â Â Â Â Â Â...
Statements: W ≤ F≤ J ≥ E > K; Z < Q ≤ J ≤ B
Conclusions :
I. W = B
II. W < B
Statements: A < B ≤ C, A > E, F ≤ B < D
Conclusions:
I. D > A
II. E < B
III. C > E
IV. D > C